Assessing the potential for tertiary nitrification in sub-surface flow constructed wetlands. Issue 1 (1st January 2016) - Butterworth, Eleanor; Richards, Andrew; Jones, Mark; Dotro, Gabriela; Jefferson, Bruce
Abstract : The challenge of how to maintain or improve wastewater treatment performance without causing an excessive increase in energy or costs is increasingly focussed towards ammonia. On small sewage treatment works, solutions have historically been energy intensive: to divert waste to a larger plant, add a polishing step to the end of the process flow sheet or upgrade and replace upstream processes. Constructed wetlands (CWs) offer a low energy alternative to meet these challenges. This review explores oxygen transfer theory; nitrification performance of existing CW systems, and the key affecting factors to be considered when implementing the technology for tertiary treatment upgrades. Future perspectives include the use of artificial aeration and greater consideration of vertical sub-surface flow systems as they achieve the nitrification capacity in a smaller footprint than horizontal flow systems and, where suitable hydraulics permit, can be operated under very low energy demand.